Esensi dan Signifikansi Studi Tafsir Madzhabi bagi Civitas Akademika Muslim - Wildah Nurul Islami (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The essence and significance of the study of madzhabi interpretation for the Muslim academic community. This article examines the essence, scope, and significance of the study of madzhabi interpretation for the Muslim academic community by focusing on the study of the theology verses of different mufassir ideologies, which influence the results of the interpretation of the Qur'an in the resulting exegesis. Using descriptive analysis techniques, the author found that there are different characteristics of the existing madzhabi tafsir books, both shi'ah, mu'tazilah, khawarij and Sunni. However, these four exegesis also have an element of similarity in terms of the subjectivity of interpreters in interpreting the verses of the Qur'an and elements of equal importance for mutual legitimacy of the madzhab it embraces. Tafsir madzhabi is part of madhahib al-tafsir (tafsir pattern) is viewed in terms of the tendency of madzhab embraced by mufassir. The initial framework of understanding the study of madzhabi interpretation is to study two aspects of science, namely kalam science and tafsir science. Kalam science is a science that discusses the creed of Imani (the nature and nature of Allah, the problems of the world and death based on Islamic doctrine), while the science of tafsir is a science that examines the meaning of Allah's kalam in the Qur'an in accordance with the abilities possessed by humans. With the study of madzhabi interpretation, it is expected that the academic community can develop a discourse on the importance of respecting plurality in interpreting qur'anic verses related to differences in theological madhhab so as not to behave taqdis al-fikr al-diniy (sanctity of religious thought) for the realization of religious moderation.